Ecological Validity and Reliability of an Age-Adapted Endurance Field Test in Young Male Soccer Players. Issue 12 (December 2019) - Castagna, Carlo; Krustrup, Peter; D'Ottavio, Stefano; Pollastro, Carlo; Bernardini, Andrea; Araújo Póvoas, Susana C.
Abstract : Abstract: Castagna, C, Krustrup, P, D'Ottavio, S, Pollastro, C, Bernardini, A, and Araújo Póvoas, SC. Ecological validity and reliability of an age-adapted endurance field test in young male soccer players. J Strength Cond Res 33(12): 3400–3405, 2019—The purpose of this study was to examine the reliability and the association with relevant match activities (ecological validity) of an age-adapted field test for intermittent high-intensity endurance known as Yo-Yo intermittent recovery level 1 children's test (YYIR1C) in young male soccer players. Twenty-eight young male outfield soccer players (age 11.1 ± 0.9 years, height 142 ± 4.4 cm, body mass 37.0 ± 5.9 kg) with at least 2 years of experience in soccer competitions were tested twice using YYIR1C and an age-adapted competitive small-sided game (i.e., 9v9), 7 days apart in a random order. The YYIR1C performance showed an excellent relative (intraclass correlation coefficient = 0.94) and a good absolute reliability (typical error of measurement as percentage of the coefficient of variation = 5.1%). Very large and significant associations were found between YYIR1C performance and match high-intensity activity ( r 2 = 0.53). Large correlations were found between YYIR1C and match sprinting ( r 2 = 0.42) and high-intensity metabolic power ( r 2 = 0.46) distances. Match total distance was largely associated with YYIR1C ( r 2 = 0.30). The results of this study showed that YYIR1C may be considered a valid and reliable field test for assessing intermittent high-intensity endurance in young male soccer players. Because of the relevance of aerobic fitness in youth soccer, future studies testing the sensitiveness of YYIR1C are necessary.